A Systematic Review and Meta-Analysis of the Efficacy and Safety of Xinbao Pill in Chronic Heart Failure - Wang, Yuanping; Liu, Yuntao; Liu, Zhongqiu; Cheng, Yuanyuan; Wang, Dawei (Frontiers in Pharmacology, 2022)
Objective: This study aimed to clarify the efficacy and safety of Xinbao pill (XBP) as an adjunctive treatment for chronic heart failure (CHF). Methods: Randomized controlled trials (RCTs) on the efficacy and safety of XBP in the treatment of CHF were searched from the six databases. The risk of bias assessment tool recommended by Cochrane Handbook 5.1 were used to assess the methodological quality of the included studies. RevMan 5.3 software was used for meta-analysis. The subgroup and sensitivity analyses were also performed. The grading recommendations assessment, development, and evaluation (GRADE) technique were used to assess the evidence's certainty. Results: Nine RCTs with a total of 882 patients were identified in this study. The meta-analysis demonstrated that XBP as adjunctive therapy was superior to conventional medicine alone for the treatment of CHF in improving the left ventricular ejection fraction (LVEF; MD = 5.34; 95% CI 4.68 to 5.99; p < 0.001), the total effective rate (RR = 1.21; 95% CI, 1.14 to 1.29; p < 0.001), the cardiac output (MD= 0.56; 95% CI 0.42 to 0.70; p < 0.001), the stroke volume (MD =3.42; 95% CI 2.03 to 4.81; p <0.001) and the six-minutes walking distance (6-MWD; MD= 31.95; 95% CI 21.83 to 42.06; p <0.001), meanwhile reducing the left ventricular end-diastolic diameter (LVEDD; MD=-3.22; 95% CI -4.03 to -2.42; p < 0.001) and left ventricular end-systolic dimension (LVESD; MD=-2.93; 95% CI -3.80 to -2.06; p < 0.001). Regarding safety, a total of 2.4% (11/456) adverse reactions occurred in the XBP groups while 3.9% (18/456) in the control group. The outcomes' evidentiary quality ranged from "very low" to "moderate". Conclusions: This study indicated that XBP as adjunctive therapy combined with conventional medicine seemed to be safe and more effective than conventional medicine alone in treating CHF. However, due to the poor methodological quality of the included RCTs, further well-designed RCTs are required to confirm the efficacy and safety of XBP.